Вплив сучасних чинників на розвиток операційного менеджменту і планування на підприємстві - Плотніченко, Світлана Романівна; Беззубко, Борис Ігорович; Нехай, Вікторія Василівна; Plotnichenko, Svitlana; Bezzubko, Borys; Nekhai, Viktoriia (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Операційний менеджмент є одним із ефективних інструментів організації управління та виробничого процесу, який дозволяє контролювати виконання всіх операцій на підприємстві. Актуальним стає вивчення впливу тенденцій та факторів на планування та операційний менеджмент з метою розробки ефективних програм та процесів з управління ресурсами, операціями та основними бізнес-процесами. Метою статті є визначення впливу сучасних чинників на розвиток операційного менеджменту та планування. У статті встановлено основні чинники впливу на здійснення операційного менеджменту та планування: зростання рівня інформаційно-технічного забезпечення, впровадження цифрових технологій; корпоративна культура; дослідження в області загального управління якістю (TQM) та реінженірінгу (BPR); вплив екологічних вимог. У сучасних умовах необхідно враховувати наявні тенденції і чинники впливу на розвиток операційного менеджменту та планування. Це відкриває перспективу для подальшого зростання конкурентоспроможності підприємств, підвищить ефективність здійснення операційної та планової діяльностей. /// EN: The relevance of this article is related to the fact that operational management is one of the effective tools for organizing management and the production process, which allows controlling the execution of all operations at the enterprise. It is becoming relevant to study the impact of trends and factors on planning and operational management in order to develop effective programs and processes for managing resources, operations, and key business processes. The purpose of the article is to determine the impact of modern factors on the development of operations management and planning. The authors briefly review the evolution of research in the field of operations management. This allows us to identify the components of the overall system of an organization's operations and the place of operations management in the management system. The content of operational management is well defined by the “5Ps of operational management” model. The authors specify five key operational resources. The article examines the main factors influencing the development of operational management: growth in the level of information and technical support, the introduction of digital technologies, corporate culture, research in the field of total quality management (TQM) and business process reengineering (BPR), and the influence of environmental requirements. For each factor, the characteristics of development and impact on operational management are identified. The common features and differences between TQM and BPR are identified. The study allowed us to conclude that the role and importance of operational management i and planning s increasing. In modern conditions, it is necessary to take into account existing trends and factors influencing the development of operational management. and planning. This opens up prospects for further growth in the competitiveness of enterprises and will increase the efficiency of operational and planned activities.
Influence of modern factors on the development of operational management and planning at the enterprise
Keywords: операційний менеджмент; цифровізація; операційні процеси; операція; планування; operations management; digitalization; operational processes; operation; planning